2016
DOI: 10.1002/jnr.23847
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem cell transplantation and lentiviral vector‐based gene therapy for Krabbe's disease: Present convictions and future prospects

Abstract: Currently, presymtomatic hematopoietic stem and progenitor cell transplantation (HSPCT) is the only therapeutic modality that alleviates Krabbe's disease (KD)‐induced central nervous system damage. However, all HSPCT‐treated patients exhibit severe deterioration in peripheral nervous system function characterized by major motor and expressive language pathologies. We hypothesize that a combination of several mechanisms contribute to this phenomenon, including 1) nonoptimal conditioning protocols with consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Here, we used optimized transduction protocol resulting in VCN values that are 2-10-fold higher than VCN reported in a previous study evaluating the LV-mediated expression of chimeric GALC enzymes in HSPCs (Hu et al, 2016). Our results show that the addition of the IDSsp and ApoE II peptide did not modify the expression, secretion, or activity of the GALC enzymes in vitro.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Here, we used optimized transduction protocol resulting in VCN values that are 2-10-fold higher than VCN reported in a previous study evaluating the LV-mediated expression of chimeric GALC enzymes in HSPCs (Hu et al, 2016). Our results show that the addition of the IDSsp and ApoE II peptide did not modify the expression, secretion, or activity of the GALC enzymes in vitro.…”
Section: Discussionmentioning
confidence: 69%
“…ApoE II shows a higher efficacy as compared to ApoB or ApoE I in enhancing the transport across the BBB of the IDUA enzyme in MPS I mice (Wang et al, 2013) and the enhanced correction of CNS pathology by a chimeric IDS enzyme in a murine model of MPS II (Gleitz et al, 2018). Previous studies reported the generation of chimeric GALC enzymes (Zhang et al, 2008;Hu et al, 2016;Pan et al, 2019). However, their efficacy has been mainly evaluated in cell lines (i.e., 293T, HeLa cells) or fibroblasts (from normal donors and GLD patients), while their safety and efficacy in NPCs, HSPCs, and progeny -therapeutically relevant cells types -has not been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As of today, there is a lack of therapies that can allow an ultimate resolution of LSDs but only symptomatic palliative and supportive treatments. During the past decades, experimental approaches aimed at restoring or substituting the deficient enzymatic activity have been formulated and tested: Enzyme replacement therapy (ERT), gene therapy, and hematopoietic stem cell transplantation are just a few remarkable examples [80,81,82,83,84,85,86,87]. Among these, ERT is the most tested approach as it is based on the periodic injection of human lysosomal enzymes produced by recombinant DNA techniques and then purified.…”
Section: Biodegradable Nps In Drug Delivery Systemsmentioning
confidence: 99%